The Ecuadorian Microbiome Project: a plea to strengthen microbial genomic research - Díaza, Magdalena (2021)
A technological revolution provides nations with access to unprecedented quantities of molecular information, and this is particularly evident in the vast and yet poorly understood realm of the microbiome. Traditionally, many developing countries in Asia, Africa, and South America remain marginal participants in the global flow of biodata, which will eventually affect their productivity and economies. Here, we present the Ecuadorian Microbiome Project (EcuMP) as an integrative initiative to close the research gap in the microbiome for Ecuador. We discuss the relevance that the study of the microbiome has for our understanding of diversity and new forms of production and biocapital. We also evaluate the state of research in metagenomics and the microbiome for South America, with emphasis on Ecuador as a small but biodiverse country. In the strict sense of access, understanding, and technological innovation based on molecular data, we propose the definition of bioliteracy. As indirect estimates of bioliteracy, we measured the number of indexed publications, BioProjects, monthly global internet traffic to GenBank, and patent applications in Espacenet. South America has a notable unevenness in scientific productivity related to the microbiome and metagenomics. Brazil leads productivity, with most of the measured parameters remaining one order of magnitude higher than other countries in the region. Participation of South American countries in the global flow of genomic information dwarfs when compared to the US. To reduce the effects of technological dependency and the associated lack of economic productivity, Ecuador should address the technological gap in the study of the microbiome. Our assessment reveals the urgency to translate the study of microbiomes into a source of technological prowess and the basis for local biocapitals.